Social and philosophical aspects of the power of information and knowledge in modern society (Journal of Philosophy Culture and Political Science, 2018)
The article analyzes the exerted influence on modern society informatization process, indicated the high role of information exposed to contemporary social structures change. The analysis of the concepts of «information» and «knowledge» in major foreign and domestic investigations. Clarifies their basic meanings in the science of man. The analysis and presentation of the basic characteristics of knowledge. Given the differences between the concepts of «information» and «knowledge», highlighted a number of important issues. With cultural and social and economic points of view, the term «global information society» due to the continuous increase in the growth of information and knowledge involves the concept of «information industry». At the present stage of information and knowledge certainly are a valuable resource. However, do not go unheeded, and the flow of information, which can be an obstacle to human values. The authors present new ways of organizing and managing the economy, based on knowledge. The purpose of information is understood as a global rationalization of intellectual activity.Key words: information, information, education, information society, information industry, audiovisual culture, philosophy, power, globalization, intelligence.